Al cuore dell’agire. Rilevanza del timico per le passioni - Migliore, Tiziana (Rivista Italiana di Filosofia del Linguaggio, 2020)
This article proposes a reconception of the thymic category in semiotics and philosophy. The nature of ϑυμός (thymós) to be a mix of venous and arterial fluids on the one hand and of temperaments on the other, has diverted current philosophy and social sciences from field studies focused on the effects of ϑυμός on behaviour and in personal decisions. Yet this the sphere of passions related to the physical structure of the human organism, which depends in part on the character of the individual, in part on cultural norms, habits and social judgments, has a significant impact on the perception that man has of his own body and of the external world, on the formation of tastes and distastes, and the transformation of senses into values. By examining the notion of ϑυμός in Greek tradition – in literature, philosophy, medicine and rhetoric, with the enthymeme – we will demonstrate its function as the psychosomatic “motivation” to act. It can be grasped in the coming and going between enunciation and semantics at a deep level, as it exposes personality effects on the person.